An Overview of Social Skills Education for Adolescents with Autism Spectrum Disorder - Thao Thi Do; Thi, Anh Thu Nguyen; Nguyen, Hoa Thi (Journal of Ecohumanism, 2024)
Adolescents with Autism Spectrum Disorder (ASD) often encounter difficulties in developing and applying social skills, which are crucial for their success in daily interactions and overall well-being. This paper provides an overview of existing social skills education programs designed for adolescents with ASD, examining the theoretical foundations, teaching strategies, and their impact on social competence. Additionally, the paper offers recommendations for practitioners and educators aiming to implement effective social skills interventions to support adolescents with ASD.